Online Location of Faults on AC Cables in Underground Transmission Systems - Jensen, Christian Flytkjær (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
This book reports on various techniques for fault location on crossbonded cables, identifies the best method and describes the construction of a full fault locator system. The developed system is able of pinpointing the fault location on long cross-bonded cable systems and will be installed in Danish substations for monitoring the coming cable-based transmission grid. The work was conducted as part of a collaborative project between the department of energy technology at Aalborg University and the Danish transmission system operator for electricity and natural gas, Energinet.dk.  .